2017
DOI: 10.1111/jvh.12791
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Core‐ and Polymerase‐derived immunogenic peptides included in novel therapeutic vaccine by T cells from Chinese chronic hepatitis B patients

Abstract: SummaryChronic hepatitis B (CHB) is one of the major public health challenges in the world.Due to a strong interplay between specific T-cell immunity and elimination of hepatitis B virus (HBV), efforts to develop novel immunotherapeutics are gaining attention. TG1050, a novel immunotherapy, has shown efficacy in an animal study. To support the clinical development of TG1050 in China, specific immunity to the fusion antigens of TG1050 was assessed in Chinese patients. One hundred and thirty subjects were divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“… 83 , 84 New approaches to therapeutic vaccines include the use of viral vectors, antigens from HBV core or polymerase regions, and combination with immune checkpoint inhibitors. 83 88 A phase 1b/2a trial of Chimpanzee adenoviral and modified vaccinia Ankara viral vectors encoding multiple HBV antigens (ChAdOx1-HBV/MVA-HBV) used in a prime-boost strategy in virally suppressed patients showed that the addition of low-dose nivolumab (programmed death receptor-1 inhibitor) resulted in greater HBsAg decline (mean 1 log 10 at 6 months) and 1 patient lost HBsAg lasting 8 months after the last dose. 89 …”
Section: New Therapies Aimed Toward Hbv Curementioning
confidence: 99%
“… 83 , 84 New approaches to therapeutic vaccines include the use of viral vectors, antigens from HBV core or polymerase regions, and combination with immune checkpoint inhibitors. 83 88 A phase 1b/2a trial of Chimpanzee adenoviral and modified vaccinia Ankara viral vectors encoding multiple HBV antigens (ChAdOx1-HBV/MVA-HBV) used in a prime-boost strategy in virally suppressed patients showed that the addition of low-dose nivolumab (programmed death receptor-1 inhibitor) resulted in greater HBsAg decline (mean 1 log 10 at 6 months) and 1 patient lost HBsAg lasting 8 months after the last dose. 89 …”
Section: New Therapies Aimed Toward Hbv Curementioning
confidence: 99%